Statistics Notes for Cornwall - Hodgson, Natasha (The University of Hull)
The content, format, and level of ambiguity in the Domesday statistics can vary from county to county. These Statistics Notes aim to provide the information essential to their understanding for each county. The topics discussed are: Previous studies; Domesday circuits; the Domesday county; Satellite texts; Duplicates; Boroughs; Geld (tax); Ploughlands; Ploughteams; Population; Woodland; Meadow; Pasture; Values; Waste. The file concludes with the aggregated totals of the major statistics for the county, together with the totals compiled by previous authors, plus notes attempting to explain the discrepancies between these and our own totals.